Evaluation of the pharmacokinetics and pharmacodynamics of two leuprolide acetate 45 mg 6‐month depot formulations in patients with prostate cancer. Issue 4 (9th May 2014) - Mostafa, Nael M.; Chwalisz, Kristof; Larsen, Lois; Mattia‐Goldberg, Cynthia; Spitz, Aaron; Pradhan, Rajendra S.
Abstract The pharmacokinetics (PK) and pharmacodynamics of two leuprolide acetate (LA) 45 mg 6‐month depot formulations were characterized in prostate cancer patients. Subjects (planned N = 150 in each cohort) received two intramuscular injections of LA Formulation‐A or Formulation‐B administered 24 weeks apart. Samples were collected for the measurement of testosterone, LH (all subjects) and leuprolide (in a subset of subjects approximately N = 24 in each cohort) at the same time points. Leuprolide PK profile showed an initial peak followed by a rapid decline over the first week post‐dose, with mean leuprolide concentrations staying relatively constant through the end of 24‐week period. Mean testosterone and LH serum concentrations showed initial increases above baseline values after the first dose and then decreased to 16.0 ng/dL and 0.6 mIU/mL by Week 4 for Formulation‐A and were maintained at ≤14.3 ng/dL and 0.4 mIU/mL, thereafter, with negligible mean increases after the second dose. Formulation‐A showed a lower initial peak and higher leuprolide concentration during the sustained release phase which may explain higher testosterone suppression rates for Formulation‐A compared to Formulation‐B. Differences in PK between LA depot formulations were reflected in pharmacodynamic responses, with a higher rate of testosterone suppression and less escapes and acute‐on‐chronic responses for Formulation‐A.